An automated approach to nacelle parameterization using intuitive class shape transformation curves - Christie, Robert; Heidebrecht, A.; MacManus, David G. (American Society of Mechanical Engineers (ASME), 2017)
A tool to create parametric aerodynamic shapes using intuitive design variables based on class shape transformation (CST) curves is presented. To enable this, a system has been developed which accepts arbitrary constraints and automatically derives the analytical expressions which describe the corresponding class shape transformation curves. Parametric geometry definitions for fan cowl and intake aero-lines were developed using the generalized method. Computational fluid dynamics (CFD) analysis of the fan cowl shows that despite the simple geometry definition, its performance characteristics are close to what would be expected of a finished design. The intake geometry was generated in a similar way and met the typical performance metrics for conventional intakes. This demonstrates the usefulness of the tool to quickly and robustly produce parametric aero-lines with good aerodynamic properties, using relatively simple intuitive design variables.